2019
DOI: 10.1111/php.13090
|View full text |Cite
|
Sign up to set email alerts
|

A Cyanine Photooxidation/β‐Elimination Sequence Enables Near‐infrared Uncaging of Aryl Amine Payloads

Abstract: Uncaging strategies that use near-infrared wavelengths can enable the highly targeted delivery of biomolecules in complex settings. Many methods, including an approach we developed using cyanine photooxidation, are limited to phenol-containing payloads. Given the critical role of amines in diverse biological processes, we sought to use cyanine photooxidation to initiate the release of aryl amines. Heptamethine cyanines substituted with an aryl amine at the C4 0 position undergo only inefficient release, likely… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
38
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(39 citation statements)
references
References 37 publications
0
38
0
Order By: Relevance
“…The group of Schnermann has exploited the photooxidation of NIR absorbing cyanine dyes, to generate a range of photocleavable linkers, which can be used to construct photolabile antibody-drug conjugates (ADC). [28,113,114] Irradiation leads to cyanine photooxidation, formation of a dioxetane ring on the heptamethine bridge and subsequent cleavage to a conjugated Figure 6. Molecular design of a 2PA dyad capable of acetic acid (red) release, combining a nitroindolinyl photocage (pink) and a dissymmetric 2PA chromophore (blue).…”
Section: Photochemical Bond Cleavage: "Photo-uncaging"mentioning
confidence: 99%
“…The group of Schnermann has exploited the photooxidation of NIR absorbing cyanine dyes, to generate a range of photocleavable linkers, which can be used to construct photolabile antibody-drug conjugates (ADC). [28,113,114] Irradiation leads to cyanine photooxidation, formation of a dioxetane ring on the heptamethine bridge and subsequent cleavage to a conjugated Figure 6. Molecular design of a 2PA dyad capable of acetic acid (red) release, combining a nitroindolinyl photocage (pink) and a dissymmetric 2PA chromophore (blue).…”
Section: Photochemical Bond Cleavage: "Photo-uncaging"mentioning
confidence: 99%
“…A cyanine conjugate designed for aryl amine photorelease conducted by Schnermann et al . provides insight into this very reaction.…”
Section: Commentarymentioning
confidence: 99%
“…The work of Schnermann et al . is a key initial step with the advent of NIR‐absorbing cyanine conjugates to photorelease aryl amines. It has been shown that the reaction involves the photorelease of anilines, but it is conceivable that new cyanine conjugates will serve as a pathway to the photorelease of other amine compounds.…”
Section: Commentarymentioning
confidence: 99%
See 1 more Smart Citation
“…Heptamethine cyanine dyes were traditionally used as reporter molecules that bind to biomolecules such as proteins, RNA, and DNA (Lipowska et al, 1993;Williams et al, 1993Williams et al, , 1997Shealy et al, 1995;Christian Mason et al, 1997;Sowell et al, 2001a,b;Strekowski et al, 2001;Patonay et al, 2004;Luciano et al, 2019). More recently, the use of a cyanine dye as a photoactivated nanocage for targeted drug release has been reported by Gorka et al 2014, Nani et al (2015aNani et al ( ,c, 2017, Sato et al (2015Sato et al ( , 2016, Patel et al (2016) and Yamamoto et al (2019). Cyanine dyes offer several advantages such as maximum absorbances in the NIR window (650-900 nm), low background absorbance interference, and low toxicity (Marshall et al, 2010;Donald et al, 2011).…”
Section: Introductionmentioning
confidence: 99%